2017
DOI: 10.18632/oncotarget.16072
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cδ1 suppresses cell migration and invasion of breast cancer cells by modulating KIF3A-mediated ERK1/2/β- catenin/MMP7 signalling

Abstract: Phospholipase C δ1 (PLCD1) encodes an enzyme involved in energy metabolism, calcium homeostasis and intracellular movement. It is located at 3p22 in a region that is frequently deleted in multiple cancers, and the PLCD1 enzyme is a potential tumour suppressor in breast cancer that inhibits matrix metalloprotease (MMP) 7, but the detailed mechanism remains elusive. In this study, we found that PLCD1 was downregulated in breast cancers, and the gain-or-loss functional assay revealed that PLCD1 inhibited cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Moreover, the induction of miR-10b expression resulted in important changes in cell morphology, EMT markers, as well as expression of cell surface receptors, ECM components, including syndecan-1, which is a target of miR-10b [44], and proteolytic enzymes such as MMP2, MMP7 and MMP9. These alterations were accompanied by the strong increase in the phosphorylated levels of Erk1/2 kinase, which has been correlated with breast cancer proliferation and motility [70], suggesting the critical role of miR-10b in this signaling pathway. Germany), or miR negative control (10nM, ABI) were performed according to the manufacturer's instructions and as described previously [47].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the induction of miR-10b expression resulted in important changes in cell morphology, EMT markers, as well as expression of cell surface receptors, ECM components, including syndecan-1, which is a target of miR-10b [44], and proteolytic enzymes such as MMP2, MMP7 and MMP9. These alterations were accompanied by the strong increase in the phosphorylated levels of Erk1/2 kinase, which has been correlated with breast cancer proliferation and motility [70], suggesting the critical role of miR-10b in this signaling pathway. Germany), or miR negative control (10nM, ABI) were performed according to the manufacturer's instructions and as described previously [47].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, PLCε knockout mice, generated by two different groups, showed contrasting oncogenic roles played by PLCε: one being pro-oncogenic [68] and the other one being anti-oncogenic [69]. Recent studies have reported PLCδ1 as a tumor suppressor in breast cancer [70] and ESCC [65]. Even as all these reports support the fact that PLCs are involved in cancer, very little has been done at the clinical level.…”
Section: Plcs In Cancer Development and Progressionmentioning
confidence: 99%
“…In cancer, alterations in cell growth, proliferation, survival and cell migration are central in the development and progression of the disease. PLCs have been demonstrated to be involved in these essential processes in cancer [70,74,75].…”
Section: Plcs In Cancer Development and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP7 is commonly expressed in ductal epithelium of exocrine glands in skin, salivary glands, pancreas, glandular epithelium of intestine and reproductive organ, liver, and breast, and is highly expressed in the luminal surface of dysplastic glands in human colorectal cancer (29). In clinical practice, MMP7 inhibitors can potentially be applied to control the invasive capacity of cancer cells (30,(32)(33)(34). In 2013, MMP7 was found to be highly expressed in advanced colorectal adenomatous and involved in converting colorectal adenomas into a malignant state and facilitating the cancer growth (35).…”
Section: Discussionmentioning
confidence: 99%